Comparison of antimicrobial susceptibility of Glaesserella parasuis from different pig production systems in Taiwan between 2015 and 2020 - Wei-Hao Lin; Zhu-Wei Liou; Szu-Min Lin; Cheng-Yao Yang; Chuen-Fu Lin; Yung-Fu Chang; Chao-Nan Lin; Ming-Tang Chiou (Porcine Health Management)
Abstract Background Glässer’s disease, caused by Glaesserella parasuis (G. parasuis), is a widespread bacterial infection in swine that leads to significant economic losses. G. parasuis, a member of the normal microbiota within the Pasteurellaceae family, exhibits horizontal resistance gene exchange and intracellular invasion capabilities, increasing the risk of developing resistant isolates. Accurate antimicrobial therapy is essential for controlling Glässer’s disease. The production systems for exotic crossbred pigs and Taiwan black pigs differ considerably. To inform Glässer disease control and monitor antimicrobial resistance, we assessed the antimicrobial susceptibilities of G. parasuis isolates, analyzed them using normalized resistance interpretation (NRI), and compared findings between the two production systems. Results A total of 154 G. parasuis isolates from 106 exotic crossbred pig herds and 48 Taiwan black pig herds were tested against 16 antimicrobial agents between 2015 and 2020. Due to the absence of specific breakpoints for G. parasuis, NRI was utilized to define non-wild-type (non-WT) populations based on minimum inhibitory concentration (MIC) distributions. Non-WT subpopulations of isolates for amoxicillin, ampicillin, ceftiofur, gentamicin, kanamycin, and tiamulin were observed. The highest MIC90 (the concentration at which 90% of isolates were inhibited) was > 256 µg/mL for several antimicrobials, including gentamicin, kanamycin, lincomycin, lincospectin, spectinomycin, and tylosin. In contrast, the lowest MIC90 was observed for ceftiofur (0.5 µg/mL). The MIC values for cephalothin were significantly higher in exotic crossbred pigs than in Taiwan black pigs (p = 0.0016). Conversely, MIC values for florfenicol were significantly higher in Taiwan black pigs than in exotic crossbred pigs (p = 0.003). Conclusions This study provides the susceptibility profile of G. parasuis isolates for both exotic crossbred pigs and Taiwan black pigs in Taiwan and highlights potential antimicrobial resistance for aminocyclitol, aminoglycosides, beta-lactams, lincosamides, macrolides, and pleuromulin. Ceftiofur, cephalothin, doxycycline, and florfenicol could be most suitable for treating early-stage Glässer’s disease. Nonetheless, increased attention should be paid to the responsible use of antimicrobials in light of the growing threat of antimicrobial resistance.